Safety Compliance in a Sample of Italian Mechanical Companies: The Role of Knowledge and Safety Climate - Federico Ricci; Chiara Panari; Annalisa Pelosi (MDPI AG, 2022)
The accident rate in the Italian mechanical sector is still too high, and evidence-based interventions to improve safety performance are essential. To better address this, our study contributes to the understanding of how to promote safety compliance through safe behaviours by using a sample of Italian mechanical workers (n = 109). Before and after scheduled safety training, intervention data on organizational factors, as well as on individual factors affecting safety-related behaviours, were collected. Particularly, data were collected using multiple sources, including self-perception questionnaires (to measure the safety climate among the management and colleagues and the safety attitude), paper and pencil tests (to measure safety knowledge), and observations by personnel with experience in observation tasks (to measure safety behaviours objectively). A model class of competing general linear models was built to determine which of the models was best suited for predicting safety-related behaviours. The results showed that both knowledge and the management's safety climate effectively promoted safety compliance. Crucial implications for the effectiveness of active teaching methods, along with the need for continuous training and the prominent role of the management team members in giving, through their actions, further relevance to the need to respect rules and procedures, were revealed. Finally, practical implications for researchers, corporate decision makers, government agencies, and international bodies are discussed.